Morphosemantic Analysis of Gyaru-go on Social Media - Kartika, Yuni; Masrokhah, Yuni (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Gyaru-go is a variety of Japanese youth language created and used by members of the Gyaru community, a Japanese subculture referring to young women aged 14-25. This study aims to identify the formation characteristics, the morphological formation processes, and the semantic meaning relations of Gyaru-go through a morphosemantic analysis. This research employs a qualitative descriptive method using a literature review technique. The research data were collected from the social media platform X during the period from June 2025 to February 2026. The results show that the most dominant formation characteristic of wakamono kotoba in Gyaru-go is shouryaku with 27 data, followed by jinbutsu zokugo with 5 data, doushi ni suru with 2 data, and sakasa kotoba with 1 data. From a morphological perspective, the most dominant formation process is clipping with 11 data, followed by compounding with 4 data, affixation with 2 data, and blending with 1 data. In addition, several combined morphological processes were identified, including clipping and blending with 6 data, clipping and affixation with 5 data, borrowing and clipping with 2 data, borrowing and blending 2 data, borrowing and affixation 1 data, and clipping and compounding 1 data. In terms of semantic meaning relation, polysemy is the most dominant type with 15 data, followed by synonyms with 14 data, hyponyms with 3 data, antonyms with 2 data, and redundancy with 1 data.